Alternative Theatre in Poland after 1989 - Ostrowska, Joanna; Tyszka, Juliusz (Journal of Applied Cultural Studies, 2016)
The term “alternative theatre” assumes the conscious adoption of a critical and rebellious attitude against the existing social and political status quo. What is more, it assumes a desire by artists of the theatre to supplant the existing methods of social communication with other, more creative ways, which better contribute to the self-development of individuals who participate in the process. Here, theatrical performance signifies the wish of theatrical artists to change the structure of their contemporaries’ perception and valorisation of the world. Bearing in mind this preliminary assumptions the authors of the article focus on the selected topics: the concept of alternative theatre, the Polish alternative theatre experience as a part of universal countercultural movement, the outdoor and site specific theatre festivals as a tool for social change and the future prospects of the alternative theatre in Poland.